Beswitched ebook - Saunders, Kate (2011)
A magic spell has spun Flora into the past. She's mysteriously swapped lives with a schoolgirl in 1935! No iPod? No cell phone? No hair products? How will she survive? Now Flora's a new girl at St. Winifred's, where she has to speak French at breakfast, wear hideous baggy bloomers, and sleep in a freezing dormitory. But lots of adventures in the past are amazing even if they are not forever. How will she find her way back to the 21st century?